The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/neuonc/nov162
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor genetic polymorphism (rs6265) is protective against chemotherapy-associated cognitive impairment in patients with early-stage breast cancer

Abstract: BackgroundBrain-derived neurotrophic factor (BDNF), a neurotrophin that regulates neuronal function and development, is implicated in several neurodegenerative conditions. Preliminary data suggest that a reduction of BDNF concentrations may lead to postchemotherapy cognitive impairment. We hypothesized that a single nucleotide polymorphism (rs6265) of the BDNF gene may predispose patients to cognitive impairment. This study aimed to evaluate the effect of BDNF gene polymorphism on chemotherapy-associated cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 45 publications
4
97
2
1
Order By: Relevance
“…[13] As several studies have shown, memory impairment is the most prominent presentation of chemotherapy-induced cognitive impairment (CICI) in patients with breast cancer, [2,4,5] and acts as an important factor affecting the long-term quality of life in these patients. [6] …”
Section: Introductionmentioning
confidence: 99%
“…[13] As several studies have shown, memory impairment is the most prominent presentation of chemotherapy-induced cognitive impairment (CICI) in patients with breast cancer, [2,4,5] and acts as an important factor affecting the long-term quality of life in these patients. [6] …”
Section: Introductionmentioning
confidence: 99%
“…It derived from data with Chinese‐based Asian cancer patients . Because the original study defined the minimal clinically important difference only for the FACT‐cog total score (4.7%‐7.2%), subsequent study by the same team chose 15% reduction as the cut‐off for the cognitive‐impairment subscale, twice the largest minimal clinically important difference for the total scale. This was a reasonably conservative cut‐off considering that average change on the impairment subscale was twice larger than other subscales .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors contribute to cognitive decline in cancer patients . Recent studies examined other risk factors: menopausal status and various endocrine therapies, health behaviors (such as exercise), cytokines, and genetic predisposing factors . Longitudinal studies investigating their effects can clarify the complex mechanisms of cognitive decline in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The APOE-gene on the other hand, encodes for Apolipoprotein E, a glycolipoprotein that plays an important role in neuronal repair and neuroplasticity [109]. More specifically, patients who carry an ε4 allele show increased neurotoxic vulnerability to chemotherapy when compared to the ones who do not [110].Polymorphisms of the BDNF (Brain-Derived-Neurotrophic-Factor)-gene were recently also associated with neuroprotection against the toxic effects of chemotherapy [111].…”
Section: Genetic Predispositionmentioning
confidence: 99%